2011
DOI: 10.1159/000326942
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Tumors with Venous Thrombosis: A Single-Institution Experience

Abstract: Objective: To assess the incidence, imaging, surgical approach and prognosis of adrenal tumors associated with venous thrombosis. Material and Methods: Charts of 206 patients who underwent adrenal surgery were reviewed. Data of patients with pathologically confirmed venous thrombosis, utilized diagnostic modalities, operative treatment and prognosis were reviewed and analyzed. Results: Venous thrombosis was confirmed pathologically in 6 patients (2.9%). All were of male gender with age ranging between 2 and 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A review of 206 patients receiving unilateral adrenalectomy for adrenal tumors found a 2.9% incidence of associated thrombosis. 48 Unlike other visceral infarcts, the adrenal gland is prone to hemorrhage, a clinical sequela that precedes or results from the infarction. A risk of recurrent hemorrhage always exists if anticoagulation therapy is restarted, although the risk of thrombosis in patients with untreated hypercoagulable disorders must be weighed against the potential for recurrent hemorrhage.…”
Section: Adrenal Infarc Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of 206 patients receiving unilateral adrenalectomy for adrenal tumors found a 2.9% incidence of associated thrombosis. 48 Unlike other visceral infarcts, the adrenal gland is prone to hemorrhage, a clinical sequela that precedes or results from the infarction. A risk of recurrent hemorrhage always exists if anticoagulation therapy is restarted, although the risk of thrombosis in patients with untreated hypercoagulable disorders must be weighed against the potential for recurrent hemorrhage.…”
Section: Adrenal Infarc Tionmentioning
confidence: 99%
“…Unilateral thrombosis is often secondary to primary or secondary adrenal malignancy. A review of 206 patients receiving unilateral adrenalectomy for adrenal tumors found a 2.9% incidence of associated thrombosis . Unlike other visceral infarcts, the adrenal gland is prone to hemorrhage, a clinical sequela that precedes or results from the infarction.…”
Section: Adrenal Infarctionmentioning
confidence: 99%
“…Adrenocortical carcinoma is infrequently associated with venous tumour thrombus (2.9%) 1. Venous involvement occurs earlier in right-sided tumours due to the renal vein on the left side.…”
Section: Descriptionmentioning
confidence: 99%
“…One out of three patients with adrenocortical carcinoma presents with involvement of the venous system and inferior vena cava (IVC) thrombus (2). Tumours of the right adrenal gland are more likely to involve the IVC, due to the right adrenal vein directly draining into it (3).…”
Section: Introductionmentioning
confidence: 99%